Лечебно-профилактические свойства цинксодержащей витаминно-протеиновой добавки - Супрун, С.М.; Донченко, Г.В.; Пархоменко, Ю.М.; Харкевич, Е.С.; Курченко, И.Н.; Аретинская, Т.Б.; Степаненко, С.П.; Кравченко, О.А. (Фактори експериментальної еволюції організмів, 2014)
Aims. Preparation of zinc containing vitamin and protein supplement based on tht selection strains producers of vitamins, coenzymes and studying its effect on the performance and viability of animal productivity. Methods Morphological, physiological and biochemical properties for selection strain mycelial fungi-producing protein, vitamins и other biologically active substances have been studied, using of known methods. Modern methods have been used to for preclinical animal trials. Results. Established the strains of Fusarium sambucinum F-10011F F-139 have a high growth rate of 0.28–0.34 hour1, rich in essential amino acids, unsaturated fatty acids such as oleic, linoleic, linolenic and arachidonic have been detected. Especially valuable presence in fungi arachidonic acid which is a precursor of prostaglandins in the body of animals and humans. The biotechnology of biopreparation obtaining based on physiology-biochemical properties was developed using joint cultivation of selected strains of Fusarium sambucinum..The preparation has hight content of vitamines, unsaturated fatty acids and other biologically active substances а but and zinc nanoakvahelat. The results of preclinical testing of fungal product have revealed a positive impact not only on the growth of living biomass but also to increase to organizm resistance to various infections diseases increase bakteriatsidnoy and lysozyme aktitvnosti of blood serum, and this led to increased survival of juveniles Conclusions. The resulting protein-vitamin supplement containing zinc nanoakvahelat uгluchay biochemical and immunological characteristics of animals. The experimental data allow to predict the effectiveness of using supplements as treatment and prevention to improve performance indicators and the natural resistance of farm animals.

Key words: biotechnology, vitamins, protein, food additiv.